2009
DOI: 10.1002/jbm.a.32307
|View full text |Cite
|
Sign up to set email alerts
|

Sustained local drug delivery from a novel polymeric ring to inhibit intimal hyperplasia

Abstract: The long-term clinical success of autologous vein and synthetic vascular grafts are limited because of the development of anastomotic intimal hyperplasia (IH). We have previously published data suggesting that cyclosporine (CyA) may reduce the development of IH in a canine model (Hirko et al., J Vasc Surg 1993;17:877-887). However, systemic administration of CyA could create serious adverse effects. Therefore, it is our long-term goal to test the hypothesis that the controlled local release of CyA from a polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Indeed a number of experimental programs have exploited adventitial delivery of therapeutic agents to the vein graft to take advantage of these mechanisms. [75-78]…”
Section: Histological Remodelingmentioning
confidence: 99%
“…Indeed a number of experimental programs have exploited adventitial delivery of therapeutic agents to the vein graft to take advantage of these mechanisms. [75-78]…”
Section: Histological Remodelingmentioning
confidence: 99%
“…Previous attempts at perivascular drug delivery from polymer devices have included particles, wraps, cuffs and hybrid assemblies of PLGA, PCL, or both polymers. These attempts have aimed to regulate inflammation and proliferation with various drugs, such as rapamycin, 18,19 paclitaxel, 18,20,21 cyclosporine A, 22 and sunitinib. 23 However, clinical use of these drugs has been limited due to cytotoxicity, which merits the development of a drug delivery approach focused on SPM (e.g., RvD1).…”
Section: Introductionmentioning
confidence: 99%
“…Despite several theoretical advantages [ 11 , 12 , 13 , 14 , 15 ], a perivascular drug delivery device should resolve several challenges in terms of inflammatory change to the treated tissue after degradation, the influence of vascular constriction, controlled drug release, ease of application, or drug localization. In our previous study [ 22 ], a highly flexible and porous silk fibroin MN wrap was shown to enhance cell compatibility and maintain the biological and structural unity of vascular tissue with minimal deformation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, different forms of external vascular devices such as films, wraps, depot gels, meshes, rings, or microparticles/nanoparticles were reported for perivascular delivery of an antiproliferation drug such as paclitaxel or sirolimus to prevent neointimal hyperplasia [ 11 , 12 , 13 , 14 , 15 ]. In our previous studies, an external applicable perivascular microneedle (MN) device with paclitaxel and sirolimus showed appropriate drug distribution in vascular tissue and significantly decreased neointimal hyperplasia of the abdominal aorta in a rabbit balloon injury model [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%